A highly efficient heterogeneous aerobic alcohol oxidation catalyzed by immobilization of bipyridine copper(I) complex in MCM-41. Issue 46 (18th November 2015) - Zhao, Hong; Chen, Qiurong; Wei, Li; Jiang, Yuanyuan; Cai, Mingzhong
Abstract: A heterogeneous copper(I)-catalyzed aerobic oxidation of primary benzylic and allylic alcohols to aldehydes was achieved under air in EtOH at 50 °C in the presence of 5 mol % of MCM-41-immobilized bipyridine copper(I) complex [MCM-41-bpy-CuI] and 5 mol % of 2, 2, 6, 6-tetramethylpiperidine- N -oxyl (TEMPO) using aqueous ammonia as base, yielding a variety of aromatic and α, β-unsaturated aldehydes in good to excellent yields. This heterogeneous copper catalyst can be easily recovered by a simple filtration of reaction solution and reused for at least 10 consecutive trials without any decreases in activity. The use of recyclable heterogeneous copper catalyst and green reagents, such as air as oxidant and ethanol as solvent, made the system attractive for environmentally sustainable processes. Graphical abstract: